Article Review: Moringa Plant (Moringa oleifera Lamk.) as a New Candidate for Anti-Acne - Raissa, Talitha Hasna; Rosmalina, Agriana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Acne is an abnormal skin condition caused by excessive production of oil glands (sebaceous glands), which causes blockage of hair follicle ducts and skin pores. Acne occurs due to various factors, one of which is bacterial infection. The bacteria that cause acne are Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus. The moringa plant (Moringa oleifera Lamk.) is also known to have potential antibacterial activity against bacteria that cause acne. This research aims to determine the benefits of moringa plant as a new candidate for anti-acne. This research uses the Systematic Literature Review method by collecting data through databases such as Publish or Perish, PubMed, and Google Scholar. The results of this review article show that Moringa oleifera Lamk. leaf extract has been proven to have potential as a new candidate for anti-acne, which is characterised by the formation of an inhibition zone. Moringa leaf 96% ethanol extract using the well method best inhibits the growth of Propionibacterium acnes bacteria. Moringa leaf 96% ethanol extract using the disc diffusion method is more effective on Staphylococcus aureus bacteria. Moringa leaf 70% ethanol extract using the well method is more effective on Staphylococcus epidermidis bacteria.